Osiowo-Symetryczne Zagadnienie Teorii Konsolidacji w Przypadku Powierzchni Przepuszczalnej dla Cieczy - Kończak, Z. (Engineering Transactions, 1973)
The object of considerations is a consolidating halfspace loaded at the surface by a concentrated force. The theory is based on a linear theory of fluid flow through a porous deformable medium as formulated by Biot. Solution of the system of equations of the linear consolidation theory yields a formula making it possible to determine the settlement of a consolidating halfspace as a function of time. Initial conditions of the problem, satisfied by the solution, are discussed; the conditions are not fulfilled by the solutions known earlier. The relation between the solution presented and that by Boussinesq (known from elasticity) is shown. At P=1 the solution derived becomes Green's function and thus may be used to construct the solutions for arbitrarily distributed, time-dependent loading of the surface. A qualitative illustration of the solution is presented in the form of graphs made for fluid- saturated sandstone, for times t=0, t=1 s., t=1 h. and t tending to infinity.